AN ANALYSIS OF SINGAPOREAN AND INDONESIAN MATHEMATICS CURRICULA AND THEIR IMPLICATIONS BASED ON BLOOM’S TAXONOMY - Nadia Risqi Sabita; Santika Lya Diah Pramesti (PHI: Jurnal Pendidikan Matematika, 2026)
This research is motivated by the discrepancy in numeracy literacy achievements between Singapore and Indonesia in PISA studies. The objective is to analyze the comparative distribution of cognitive levels in the mathematics curriculum of both countries based on Bloom's Taxonomy and its implications for learning quality. This research employs a qualitative method with content analysis of the Indonesian Kurikulum Merdeka (Phase D) and the Singaporean Mathematics Syllabus (Secondary School). The results show that the Indonesian curriculum is dominated by the C3 level (Applying) at 40%, emphasizing procedural skills. In contrast, the Singaporean curriculum is dominated by the C5 level (Evaluating) at 30%, requiring mathematical reasoning and justification. The conclusion indicates that Singapore's curriculum is stronger in integrating Higher Order Thinking Skills (HOTS). Consequently, Indonesian policy developers should redesign Learning Outcomes by increasing the proportion of C4 and C5 levels to foster students' critical thinking skills.